Comparison between second generation HydroSoft coils and bare platinum coils for the treatment of large intracranial aneurysms - Tessitore, Agostino; Paolucci, Aldo; Hohenstatt, Sophia; Caragliano, Antonio A; Buonomo, Orazio; Mormina, Enricomaria; Pitrone, Antonio; Vinci, Sergio L (Interventional neuroradiology, 2022)
BackgroundThe development of HydroSoft coils (HSC) aims to reduce the high recurrence and retreatment rates observed in large brain aneurysms by improving primary brain aneurysm filling and thus occlusion efficacy. We compared clinical and angiographic effectiveness of bare platinum coils (BPC) versus second generation HSC for large intracranial aneurysms at our center.MethodsWe included 61 large aneurysms between 2015 and 2018, 29 embolized primarily using HSC and 32 treated with BPC. The aneurysm occlusion rates were assessed after 3 and 12 months with an MRI scan and at 6 moths with a control digital subtraction angiography (DSA) using the Raymond-Roy occlusion classification (RROC). Clinical outcomes were evaluated using the modified ranking scale (mRS).ResultsThe observed immediate occlusion rate was slightly better in the BPC group, however, this group had a significant increase of progressive reperfusion at all imaging follow-up. Contrarily, the rate of complete occlusion increased significantly in the HSC group, starting from the 6 and 12-months follow-up. 7 aneurysms (11.4%) were re-treated (15.6% BPC and 6.9% HSC). The 6 and 12-months clinical data showed mRS score 0-1 in 96.7% of patients.ConclusionsIn our single-center experience, the second generation HydroSoft coils were shown to be safe and effective for endovascular treatment of large intracranial aneurysms with encouraging clinical and angiographic results, also for ruptured aneurysms. Even if the validity is limited due to our small cohort size, HSC showed a significantly lower rate of recurrence at mid-term follow-up when compared to BPC.
Gesehen am 21.03.2023